Ising-type Magnetic Anisotropy in CePd2As2 - M. O. Ajeesh (Nature Portfolio, 2017)
Abstract We investigated the anisotropic magnetic properties of CePd2As2 by magnetic, thermal and electrical transport studies. X-ray diffraction confirmed the tetragonal ThCr2Si2-type structure and the high-quality of the single crystals. Magnetisation and magnetic susceptibility data taken along the different crystallographic directions evidence a huge crystalline electric field (CEF) induced Ising-type magneto-crystalline anisotropy with a large c-axis moment and a small in-plane moment at low temperature. A detailed CEF analysis based on the magnetic susceptibility data indicates an almost pure |±5/2〉 CEF ground-state doublet with the dominantly |±3/2〉 and the |±1/2〉 doublets at 290 K and 330 K, respectively. At low temperature, we observe a uniaxial antiferromagnetic (AFM) transition at T N  = 14.7 K with the crystallographic c-direction being the magnetic easy-axis. The magnetic entropy gain up to T N reaches almost R ln 2 indicating localised 4 f-electron magnetism without significant Kondo-type interactions. Below T N , the application of a magnetic field along the c-axis induces a metamagnetic transition from the AFM to a field-polarised phase at μ 0 H c0 = 0.95 T, exhibiting a text-book example of a spin-flip transition as anticipated for an Ising-type AFM.